Candida virulence and ethanol‐derived acetaldehyde production in oral cancer and non‐cancer subjects. (13th September 2016) - Alnuaimi, AD; Ramdzan, AN; Wiesenfeld, D; O'Brien‐Simpson, NM; Kolev, SD; Reynolds, EC; McCullough, MJ
Abstract : Objectives: To compare biofilm‐forming ability, hydrolytic enzymes and ethanol‐derived acetaldehyde production of oral Candida isolated from the patients with oral cancer and matched non‐oral cancer. Material and Methods: Fungal biofilms were grown in RPMI‐1640 medium, and biofilm mass and biofilm activity were assessed using crystal violet staining and XTT salt reduction assays, respectively. Phospholipase, proteinase, and esterase production were measured using agar plate method, while fungal acetaldehyde production was assessed via gas chromatography. Results: Candida isolated from patients with oral cancer demonstrated significantly higher biofilm mass ( P = 0.031), biofilm metabolic activity ( P < 0.001), phospholipase ( P = 0.002), and proteinase ( P = 0.0159) activity than isolates from patients with non‐oral cancer. High ethanol‐derived acetaldehyde‐producing Candida were more prevalent in patients with oral cancer than non‐oral cancer ( P = 0.01). In univariate regression analysis, high biofilm mass ( P = 0.03) and biofilm metabolic activity ( P < 0.001), high phospholipase ( P = 0.003), and acetaldehyde production ability (0.01) were significant risk factors for oral cancer; while in the multivariate regression analysis, high biofilm activity (0.01) and phospholipase ( P = 0.01) were significantly positive influencing factors on oral cancer. Conclusion: These data suggest a significant positive association between the ability of Candida isolates to form biofilms, to produce hydrolytic enzymes, and to metabolize alcohol to acetaldehyde with their ability to promote oral cancer development.